2022
DOI: 10.1371/journal.pone.0278106
|View full text |Cite
|
Sign up to set email alerts
|

Mental health service utilization in a low resource setting: A qualitative study on perspectives of health professionals in Northwest Ethiopia

Abstract: Background Mental health services are advocated to move from specialized care to more integrated and accessible primary care settings. The integration of mental health into primary health services is expanding in Ethiopia. However, there is a lack of research on the perspectives of health professionals on mental health services in Ethiopia. This study aimed to explore the perspectives, views, and experiences of health professionals regarding mental health services and the help-seeking behavior of people with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Interestingly, religious places were reported to be the most helpful source of treatment (39.5%) for depressive symptoms. A preference for religious and traditional healers over healthcare facilities was also reported in our previous qualitative study where seeking treatment from healthcare facilities was the last resort in the treatment-seeking pathway (Mekonen et al, 2022 ). Previous studies in Ethiopia reported that patients were comfortable taking treatments from healthcare facilities alongside religious/traditional healers (Baheretibeb et al, 2021 ).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Interestingly, religious places were reported to be the most helpful source of treatment (39.5%) for depressive symptoms. A preference for religious and traditional healers over healthcare facilities was also reported in our previous qualitative study where seeking treatment from healthcare facilities was the last resort in the treatment-seeking pathway (Mekonen et al, 2022 ). Previous studies in Ethiopia reported that patients were comfortable taking treatments from healthcare facilities alongside religious/traditional healers (Baheretibeb et al, 2021 ).…”
Section: Discussionsupporting
confidence: 64%
“…As such, mental health services coverage could be increased by utilizing the existing help-seeking pathway of religious/traditional healers. Basic mental health training for religious leaders and traditional healers could also help increase referrals to health facilities (Mekonen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These challenges stem from a scarcity of resources, an absence of standardized tools for monitoring service quality, frail health systems and the complexities of diverse cultural environments (Lund, 2018 ; Galagali and Brooks, 2020 ). Furthermore, the challenges encompass the absence of governmental prioritization of mental health, extensive distances to reach treatment facilities, inadequate availability of trained personnel and the prevailing perception that mental illness is non-life-threatening, resulting in a diminished emphasis on mental health services (Mekonen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many people in Africa suffer from mental health conditions but do not have access to the necessary care and resources to address their conditions (Nicholas et al, 2022). In Ethiopia, obstacles to the provision and use of mental health services include low mental health literacy, social stigma associated with mental illness, limited government attention (Mekonen et al, 2022), and shortage of mental health providers and poor access to mental health services (Yitbarek et al, 2021). The failure to diagnose and treat maternal depression can lead to chronic adverse outcomes for children, including malnutrition, poor mental, psychosocial, and physical health, premature death, and violates their basic rights (Mokwena, 2021).…”
mentioning
confidence: 99%